2018
DOI: 10.1530/joe-17-0656
|View full text |Cite
|
Sign up to set email alerts
|

The androgen receptor in bone marrow progenitor cells negatively regulates fat mass

Abstract: It is well established that testosterone negatively regulates fat mass in humans and mice; however, the mechanism by which testosterone exerts these effects is poorly understood. We and others have shown that deletion of the androgen receptor (AR) in male mice results in a phenotype that mimics the three key clinical aspects of hypogonadism in human males; increased fat mass and decreased bone and muscle mass. We now show that replacement of the gene specifically in mesenchymal progenitor cells (PCs) residing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In accordance with our observation, testosterone was shown to inhibit adipogenic differentiation of a 3T3-L1 cell line (Singh et al, 2006), and to reduce proliferation of adipocytes (Ray et al, 2008). Moreover, dihydrotestosterone (DHT) inhibited adipogenesis of human MSCs (Gupta et al, 2008; Russell et al, 2018). Considering the relationship between AR receptor expression and adipogenesis, it has been reported that the AR is downregulated in human MSCs by DHT under adipogenic culture conditions (Gupta et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In accordance with our observation, testosterone was shown to inhibit adipogenic differentiation of a 3T3-L1 cell line (Singh et al, 2006), and to reduce proliferation of adipocytes (Ray et al, 2008). Moreover, dihydrotestosterone (DHT) inhibited adipogenesis of human MSCs (Gupta et al, 2008; Russell et al, 2018). Considering the relationship between AR receptor expression and adipogenesis, it has been reported that the AR is downregulated in human MSCs by DHT under adipogenic culture conditions (Gupta et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone reduces proliferation capacity of adipocytes (Ray et al, 2008), and inhibits adipogenic differentiation of the 3T3-L1 cell line (Singh et al, 2006). However, 5α-dihydrotestosterone (DHT), a considerably more potent agonist of the androgen receptor than testosterone (Jakob et al, 2010), is able to inhibit adipogenic differentiation of human MSCs (Gupta et al, 2008; Russell et al, 2018). In mouse bone marrow MSCs the effects of testosterone have been shown to be mediated by the androgen receptor (AR) (Russell et al, 2018) that is expressed in an age- and sex-independent manner in almost all tissues, including bone and bone marrow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a crucial issue that is often overlooked is the role of sudden hormonal changes in facilitating the metastasis of CRPC cells, primarily to the bone marrow and brain [167,168] . Since androgen signaling plays an important role in normal physiology and cellular functions [169][170][171][172] , whole body hormone deprivation may result in systemic oxidative stress, especially in the bone marrow and brain, where the CRPC cells with an acquired redox-signaling network can find new sanctuaries and form metastatic foci, resulting in increased mortality associated with mCRPCs. Hence, potent compounds that may restore the antioxidant homeostasis in PCa patients following hormone deprivation, may not only suppress the selection of CRPC cells but may also decrease progression to metastatic CRPCs.…”
Section: Is There a Therapeutic Benefit Of Antioxidants In Crpc Progrmentioning
confidence: 99%